2020
DOI: 10.5114/aoms.2019.86898
|View full text |Cite
|
Sign up to set email alerts
|

Difference in hematocrit and plasma albumin levels as an additional biomarker in the diagnosis of infectious disease

Abstract: Introduction: In clinical practice, it has been observed that patients with severe infections show changes to their hematocrit (HCT) and serum albumin (ALB) levels. This study aimed to evaluate whether the difference of HCT and ALB (HCT-ALB) levels can be used as an additional biomarker for fast diagnosis of severe infections. Material and methods: This was a retrospective case-control study which included adult patients with severe infections, patients with non-infective conditions and healthy individuals. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The HCT-ALB level above 6.8 proves useful in distinguishing these conditions 16 . Additionally, they also observed that HCT-ALB level above 10.25 might facilitate the rapid diagnosis of severe infections 34 . Wang et al con rmed the importance of HCT-ALB levels in predicting the outcomes of elderly sepsis patients, using data from the MIMIC-IV and eICU-CRD databases 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The HCT-ALB level above 6.8 proves useful in distinguishing these conditions 16 . Additionally, they also observed that HCT-ALB level above 10.25 might facilitate the rapid diagnosis of severe infections 34 . Wang et al con rmed the importance of HCT-ALB levels in predicting the outcomes of elderly sepsis patients, using data from the MIMIC-IV and eICU-CRD databases 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The coloured bars represent mean and standard deviations obtained from literature studies. [30][31][32][33][34][35][36][37][38][39] For albumin and AAG, a second population was simulated with a 50% reduction in% CV.…”
Section: The Impact Of Drug-drug Interactions On Gefitinib Pharmacoki...mentioning
confidence: 99%
“…Blue shaded regions represent a 90% confidence interval from 2000 virtual individuals simulated (black circles) using Simcyp and the solid black line represents the mean values. The coloured bars represent mean and standard deviations obtained from literature studies [30][31][32][33][34][35][36][37][38][39]. For albumin and AAG, a second population was simulated with a 50% reduction in% CV.…”
mentioning
confidence: 99%
“…In addition to the above effects of infection, the patient’s hypermetabolic state causes increased albumin consumption, intestinal dysfunction causes increased albumin loss, and patients with chronic hypoxic diseases can cause an increase in HCT, as well as blood loss and anemia, which are all factors that cause changes in HCT-ALB. The numerical difference value between HCT (%) and ALB (g/L) levels (HCT-ALB) is highly sensitive and specific among patients with infectious diseases and is, therefore, a potential indicator for the differential diagnosis of infections [ 19 ]. The relationship between HCT-ALB and the prognosis of elderly sepsis patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%